If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(-4x-6)=-7(8x+6)
We move all terms to the left:
-7(-4x-6)-(-7(8x+6))=0
We multiply parentheses
28x-(-7(8x+6))+42=0
We calculate terms in parentheses: -(-7(8x+6)), so:We get rid of parentheses
-7(8x+6)
We multiply parentheses
-56x-42
Back to the equation:
-(-56x-42)
28x+56x+42+42=0
We add all the numbers together, and all the variables
84x+84=0
We move all terms containing x to the left, all other terms to the right
84x=-84
x=-84/84
x=-1
| b/7+1/7=15 | | 7(x+4)=-9 | | -6r-6r=-2-64 | | 2.9=5.6-0.9x | | -6r-6r=-2 | | x+-8=x+17 | | -8-3(-3n+8)=-5(2n-8)+4 | | h+6/5=12 | | b/9+1/7=10 | | 9(y-4)-7y=5(3y-2 | | 21x=411 | | 15x+1x=24+8x | | -2(2x-4)=-2 | | 46+4x=114 | | 7m-2=-2m+7 | | x-9=3+4-12 | | 421/48+41/8x=7/4(-5/4x-1) | | 22/x=11/16 | | 8(r-8)=-200 | | 8.7x-1.9x=116.96= | | (4x+15)/4=21 | | 2x^2=-7x-1 | | 3c−8=4c | | x+(x-8)=42 | | 3(x-2)=3x-3 | | -k=10+4k | | 0.6x-0.1-0.5x+4=0.34 | | 3(x)-1)=3x-3 | | 3x-+3x-2=4x-1 | | 9+5z=2z | | 2=x/12-1 | | 2/3+y-2/9=7/9 |